2019
DOI: 10.1021/acs.langmuir.9b02873
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Effects in Solvent-Free Bidisperse Polymer Brushes Investigated Using Density Functional Theories

Abstract: Solvent-free polymer-functionalized nanoparticles form a special type of colloid composed of inorganic cores self-suspended by their grafted coronas. In the absence of intervening solvent molecules, the fluidity of the system is provided by these tethered polymers as they fill the space.Here, we study the structure and interaction of neighboring polymer-grafted surfaces in the solvent-free condition using mean-field density functional theories. For opposing flat surfaces, the brush configuration and the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…Consequently, the collaborative behavior of the two polymers is observed and the longer polymers 1 are more capable to fill the middle region of the gap, while the shorter polymers 2 are more localized to the grafting bottom wall. Such a feature has been qualitatively predicted in the previous DFT study 64 and is unique to bidisperse interacting brushes in the solvent-free condition. In Figure 8a, as the gap thickness increases, the extent of mixing of the opposing brushes gradually decreases and the entropy components slightly reduce accordingly.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Consequently, the collaborative behavior of the two polymers is observed and the longer polymers 1 are more capable to fill the middle region of the gap, while the shorter polymers 2 are more localized to the grafting bottom wall. Such a feature has been qualitatively predicted in the previous DFT study 64 and is unique to bidisperse interacting brushes in the solvent-free condition. In Figure 8a, as the gap thickness increases, the extent of mixing of the opposing brushes gradually decreases and the entropy components slightly reduce accordingly.…”
Section: Resultssupporting
confidence: 72%
“…We have demonstrated that the general structural features observed are consistent with the previous DFT predictions. 64 The analyzed segmental relaxations not only qualitatively agree with relevant experimental measurements 57,65,66 but also provide a solid connection with the associated chain configuration.…”
Section: Discussionsupporting
confidence: 73%
“…An appealing alternative is provided by mean-field techniques, such as self-consistent field theory [ 10 , 29 , 30 ], integral equation theory [ 31 , 32 , 33 , 34 ], and density functional theory (DFT) [ 9 , 12 , 35 ]. The latter method has been already applied to study solvent-free polymer brushes [ 36 ]. However, to the best of our knowledge, the existing studies of solvent-free brush systems are limited to fully flexible grafted chains.…”
Section: Introductionmentioning
confidence: 99%
“…Opposing polymer brushes, i.e., systems consisting of two parallel surfaces, both grafted with chains, were also a subject of considerable interest [36]. Theoretical treatment concerned mainly the compression of such brushes [37][38][39][40][41]. Computer simulations were found to be a useful tool for studying opposing polymer brushes-structure, interaction, and friction between a pair of brushes (neutral and charged) were recently investigated [39,[42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%